2021
DOI: 10.1177/2049936121989548
|View full text |Cite
|
Sign up to set email alerts
|

Risk of infection associated with targeted therapies for solid organ and hematological malignancies

Abstract: Higher risks of infection are associated with some targeted drugs used to treat solid organ and hematological malignancies, and an individual patient’s risk of infection is strongly influenced by underlying diseases and concomitant or prior treatments. This review focuses on risk levels and specific suggestions for management, analyzing groups of agents associated with a significant effect on the risk of infection. Due to limited clinical experience and ongoing advances in these therapies, recommendations may … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
47
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(47 citation statements)
references
References 98 publications
0
47
0
Order By: Relevance
“…Neutropenia [204,208] Surrogate markers such as Serum or Bronchoalveolar Lavage Galactomannan Assay [209][210][211] Haematopoietic stem cell transplantation [204,208,212] Solid organ transplantation [202,[212][213][214] High dose corticosteroid therapy [215,216] Certain biologic response modifiers [206,217,218] outweigh the potential benefits [322]. Limited data on the cost-effectiveness are available, although a single centre study reported decreased hospital costs associated with PCT-guided antibiotic in medical ICU patient with undifferentiated sepsis [323].…”
Section: Risk Factor For Invasive Mold Infectionmentioning
confidence: 99%
“…Neutropenia [204,208] Surrogate markers such as Serum or Bronchoalveolar Lavage Galactomannan Assay [209][210][211] Haematopoietic stem cell transplantation [204,208,212] Solid organ transplantation [202,[212][213][214] High dose corticosteroid therapy [215,216] Certain biologic response modifiers [206,217,218] outweigh the potential benefits [322]. Limited data on the cost-effectiveness are available, although a single centre study reported decreased hospital costs associated with PCT-guided antibiotic in medical ICU patient with undifferentiated sepsis [323].…”
Section: Risk Factor For Invasive Mold Infectionmentioning
confidence: 99%
“…1 Ibrutinib targets Bruton tyrosine kinase (BTK), which plays a major role in B-and T-cell proliferation and survival 2 and recognition of infectious agents by the innate immune system. 3 Ibrutinib therapy has been associated with an increased incidence of several opportunistic infections, especially in the first 6-12 months after therapy initiation, [4][5][6][7] among which cytomegalovirus (CMV) end-organ disease has been anecdotally reported. 8 Nevertheless, little is known about the biology of CMV in ibrutinib-treated patients.…”
Section: Cytomegalovirus-specific T-cell Immunity and Dnaemia In Patients With Chronic Lymphocytic Leukaemia Undergoing Treatment With Ibmentioning
confidence: 99%
“…The association of infections, including TB, with therapeutic mTOR blockade in organ transplantation and cancer is well recognized (Fijalkowska-Morawska et al, 2011; Garcia and Wu, 2016; Jeon et al, 2017; Ruiz-Camps and Aguilar-Company, 2021; Tsai et al, 2007). Since mTOR signaling in phagocytes, antigen-presenting cells, and T cells is critical for their development, homeostasis and/or function, it is likely that mTOR exerts its protective effects in TB through a myriad of mechanisms impacting innate and adaptive immune responses (Lachmandas et al, 2016; Powell et al, 2012; Sinclair et al ., 2017; Weichhart et al ., 2015).…”
Section: Discussionmentioning
confidence: 99%